Determining Factors of Poverty in Indonesia: Household Analysis - Rini, Ayu Setyo; Sugiharti, Lilik (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2016)
The purpose of this study is to provide an overview of poverty in Indonesia by mapping the provinces based on economic growth and poverty rate as well as knowing the determinants of poverty in Indonesia with analysis at the household level. The analysis used secondary data from Susenas (National Socioeconomic Survey) in March 2012. Based on poverty mapping, the provinces are divided into four-quadrant and the analysis of 2007 and 2012 show quadrant position change of some provinces. There are provinces that getting better, those are Central Java and Maluku while North Sumatera, Banten, West Kalimantan, South Kalimantan, and South Sumatera show the worse condition. Analysis determinants of poverty measures probability of a household to be poor using logit regression model find that household characteristics like sex of household head, age of household head, number of household members, employment status of household head, access to credit, education of household head, access of information and communication technology, and locational (rural/urban) significantly affect the poor status of household in Indonesia.